Active interventions of dynamic lighting on human circadian rhythm and sleep quality in confined spaces - Wang, Tongyue; Li, Juanjie; Wang, Yanni; Dai, Shujian; Shao, Rongdi; Hao, Luoxi (Building and environment, 2022)
People in closed spaces without daylight for a long time are prone to circadian rhythm desynchrony and sleep disorders. To explore the effects of different lighting patterns on circadian rhythm and sleep, 20 adults were confined in an underground lab by within-subject design for four consecutive weeks with one lighting pattern per week. The static lighting pattern (SLP) was used in the 1st week, then the circadian forward lighting pattern (FLP) in the 2nd and 4th weeks, and the backward lighting pattern (BLP) in the 3rd week. Their salivary melatonin, Karolinska Sleepiness Scale(KSS),core body temperature (CBT), Pittsburgh Sleep Quality Index (PSQI), sleep latency and the number of awakenings were measured. The results showed dim light melatonin onset (DLMO) was delayed by 0.62 h during the 1st week, indicating the backward tendency of circadian rhythm but without significance (p = 0.295). In the 2 nd week, the schedule was forced to bring forward by 2 h, assisted with FLP. The BLP in the 3rd week resulted in a significant delay of 1.87 h in DLMO(p = 0.002) and lower melatonin at bedtime (p = 0.001), with progressively longer sleep latency, lower sleepiness at night and CBT when waking up, and PSQI increased day by day, meaning the gradually deteriorated sleep. In the 4th week, DLMO was significantly shifted forward by 2.13 h (p = 0.003), melatonin at bedtime was higher (p = 0.000), and sleep quality gradually improved. Lighting interventions on KSS, CBT, PSQI and sleep latency showed day-by-day cumulative effects, and the dynamic lighting interventions can help maintain circadian rhythm stability in closed spaces and adapt to shift hours. •Constant lighting in confined spaces will lead to the delay of circadian rhythm.•Nocturnal bright light may effectively delay circadian rhythm and worsen sleep.•Forward lighting pattern can advance circadian rhythm and improve sleep obviously.•There are cumulative effects of light, and light history needs to be considered.